Italian and Swedish adolescents: differences and associations in subjective well-being and psychological well-being - Garcia,Danilo; Sagone,Elisabetta; De Caroli,Maria Elvira; Nima,Ali Al (PeerJ, 2017)
Background One important aspect of subjective judgments about one’s well-being (i.e., subjective well-being: life satisfaction, positive affect, and negative affect) is that cultural features, such as, nationality seem to shape cognitive judgments about the “the ideal life.” In this comparative study we examined differences in subjective well-being and psychological well-being between Italian and Swedish adolescents and tested if the relationship between the three constructs of subjective well-being (i.e., satisfaction with life, positive affect, and negative affect) and psychological well-being was moderated by the adolescents’ nationality. Method Italian (n = 255) and Swedish (n = 277) adolescents answered to the Satisfaction with Life Scale, the Positive Affect Negative Affect Schedule, and Ryff’s Scales of Psychological Well-Being. Differences between samples were tested using a Multiple Analysis of Variance. We also conducted a multiple group analysis (Italy and Sweden) using Structural Equation Modelling to investigate the relationship between all three subjective well-being constructs and psychological well-being. Results Italian adolescents scored significantly higher in satisfaction with life than Swedish adolescents. Additionally, across countries, girls scored significantly higher in negative affect than boys. In both countries, all three constructs of subjective well-being were significantly associated to adolescents’ psychological well-being. Nevertheless, while the effect of the relationship between affect and psychological well-being was almost the same across countries, life satisfaction was more strongly related to psychological well-being among Swedish adolescents. Conclusions The present study shows that there are larger variations between these two cultures in the cognitive construct of subjective well-being than in the affective construct. Accordingly, associations between the cognitive component, not the affective component, of subjective well-being and psychological well-being differ between countries as well.
Keywords: Italy; Adolescents; Sweden; Life satisfaction; Negative Affect; Psychological well-being; Positive Affect; Subjective Well-Being